Rancang Bangun Jig and Fixture Body Valve 250 untuk Proses Milling pada Mesin CNC Milling Horizontal 4 Axis Double Pallet - Andaria .; Dhika Aditya Purnomo; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
PT. Zenith Allmart Precisindo is a national private company engaged in the foundry investment casting industry and advanced machining that accepts orders in the form of mass production. One of the component products produced is the body valve 250. This product is a component part of the butterfly valve, which is the body of the valve. The body valve 250 product has five machining processes, and these five processes are carried out on different machines. The first process is done on a manual milling machine, the second process is done on a CNC wirecut machine, the third process is done on a CNC turning machine, the fourth and fifth processes are done on different CNC milling machines. The milling process for the body valve 250 product has a weakness, which requires more CNC milling machines to process each part. This also affects the dimensions between the upper and lower shaftholes of the body valve 250 product which are not concentric. In order to help the process of finishing the body valve 250 product quickly and have accurate dimensions, jig and fixtur were made, so as to reduce the use of CNC milling machines. The method used in this study is the Ulrich method by making 3 different design concepts. This body valve 250 jig and fixture produces 12 products in 1 day with 3 shifts